Analisis Keterkaitan Alur Produksi QAD dan Inspeksi pada Pengendalian Kualitas Produk Kain PT. AP Menggunakan Metode SQC - Salsabila, Zahwa Allysa; Sukanta, Sukanta; Zahwa Allysa Salsabila (Fakultas Teknik Universitas Tulang Bawang, 2024)
Quality control is a technical and management process applied to achieve, maintain and improve product or service quality. In the context of PT. AP,that has gone through a continuous process will undergo an inspection process through the Quality Assurance (QA) department to determine the grading/quality level based on fabric defect standards in accordance with existing standards. In the process, the company strives to control and improve the quality of its products. From the statistical quality calculations, in the control chart results, the average quantity does not touch the top line or bottom line, which shows that the production process is running well. Then the cause-and-effect diagram (fishbone diagram) shows several errors made by humans, methods and machines so that the percentage of defective products can be maintained properly. This research aims to provide an overview of the extent to which the Quality Assurance (QA) department is related to quality control and improvement at PT. AP Keywords: Control chart, fabric grading, fishbone diagram, statistical quality control, Quality control.